MODEL PENGEMBANGAN EKONOMI DAERAH PESISIR DAN PULAU-PULAU KECIL MELALUI PENDEKATAN INTEGRASI MARINE-TOURISM INDUSTRY DI DESA BARU DAN BUKU LIMAU KECAMATAN MANGGAR KABUPATEN BELITUNG TIMUR - Reniati Reniati; Fadillah Sabri; Wahyu Adi (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2014)
The objectives of the KKN-PPM program can be divided into three: Community Empowerment, enhancing the role of Higher Education and providing support for Local Government. These activities are in order to solve the issues faced by coastal areas and small islands (WP3K), namely: Not optimal spatial planning and utilization in WP3K, low quality of human resources in WP3K management, limited facilities and infrastructure, not optimal empowerment of coastal resources for economic development, not optimal management of fisheries potential, not optimal development of potential and marine tourism objects, as well as pollution and environmental damage. The activities carried out to solve the problems faced by coastal areas and small islands (WP3K) include making a Master Plan for "Kampong Wisata", making signs for marine tourism villages, improving drainage systems and environmental sanitation in residential areas, religious lectures, socializing regional management plans and spatial planning for coastal and islands in Manggar District, training in clean water facility management, training school-age fishermen children in measles dance art, training in the field of entrepreneurship in the field of fishery product processing, conducting socialization on coral reef preservation, leadership training for the younger generation, socializing East Belitung's strategy as a world marine tourism destination, planting FADs, English courses for children, uploading videos to You Tube, training on changing the mindset of fishing communities, training on the quality of health and family planning, socializing the threat of marine destruction and the use of dangerous fishing gear, training on making accessories made from shells and making books.